FORMULATION AND STABILITY EVALUATION OF GELS CONTAINING CHITOSAN MICROPARTICLE-LOADED BEETROOT (BETA VULGARIS, LINN) FOR TOPICAL SKIN BRIGHTENING - SUKMAWATI, ANITA; WAHYUNINGRUM, SHINTA JANNATI; UTAMI, MAGHFIRATUL LAILIYAH (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of this research is to investigate the effect of Hydroxypropyl Methylcellulose (HPMC) concentration as a gel base for chitosan microparticle-containing beetroot (Beta vulgaris, Linn) toward gels stability and skin brightening effect. Methods: Ionic gelation was used to make microparticle using chitosan 1% solution and beetroot dry extract as active component. Scanning Electron Microscope (SEM) and active substance loading were used for physical characterisation. The MP then was added to HPMC-based gels at 0.5, 1.0, and 1.5% w/w. Gels were tested for viscosity, pH, and active component stability. Gels were tested for skin lightening on humans. Results: Results reveal beetroot extract may be loaded into chitosan microparticle with a Drug Loading (DL) of 23.27±0.057% w/w. HPMC gels had a pH of 5-5.4 and increased viscosity related with HPMC content. Gels showed colour instability after 6 cooling-heating cycles and decreased betanin levels on day 7 at 40±2 °C and RH 75±5%. HPMC 0.5% gel brightened human skin more than other HPMC gels. Conclusion: The 0.5% HPMC gel base had the smallest betanin reduction during the accelerated stability test, compared to the 1.0 and 1.5% HPMC gels. The formulation of chitosan microparticle gel loading beetroot extract with 0.5% HPMC gel base had brightened skin better than the other two formulae.